Geospatial dangers to countries A study of cyber security and its impact on the geo-cyber situation in Libya (Journal of Libya for geographical studies, 2023)
The cyber domain in the Arab region, with its failure and the collapse of government institutions in those countries, is witnessing a state of decline in modernity, while it pretends to play politically in other countries, such as the case of Egypt and Tunisia, as simple as the development of foundations, the civil nature of its people, and a science that collected the uses of the "cyber domain" Between the political and military role in the Syrian case, and the region was exposed through the cyber domain to psychological wars aimed at influencing the critical mass of young people through social networks, whether by parties on the basis of political, religious or sectarian differences, and on the other hand, external forces practiced “cyber” intervention to influence On security and stability, whether by feeding sectarian conflicts, so this study focused on studying cybersecurity and its relationship to geopolitics, what is the position of Libya in cybersecurity, what are the risks to which Libya was exposed, and what are the future risks in the event of not protecting its geo cyber sphere.
Keywords: cyber security; geospatial space; political geography; cyber terrorism; cyber threats